Estudio de factibilidad para la creación de la compañía de seguridad privada O.S.S. Security operational security sistems en la ciudad de Quito. - CABEZAS MOREANO, FRANKLIN RAMIRO (2012)
The present study aims to determine the feasibility of creating the Private Security Company "OS.S. SECURITY CIA LTDA., Which will be centered in the northern sector operation of the Metropolitan District of Quito. The starting point of the project was implemented surveys for both supply and demand for private security services in the city of Quito. From the results obtained by conducting a market study determined the level of unmet demand, customer payment capacity and the percentage of coverage of the future company. Was also established macro and micro location of the project. The technical study, helped to define the size of the project depending on factors such as: market, availability of financial, human, technological, etc. Through organizational study, we investigated the hierarchical structure of the company, levels of communication, functions to be performed by each of the members of the same and the distribution of spaces. Thanks to the financial study defined the various budgets that will allow the operation of the company's future; we calculated the financial evaluation variables, which allowed us to make decisions about the feasibility of the project. Finally the analysis result has allowed us to make findings and recommendations.